Analyzing the value chain for vegetables in the North-Eastern part of Bangladesh - Md. Mostafizur Rahman; Swarup Barua; Deyi Zhou; Teng Li; Md. Shaikh Farid (Cogent Business & Management, 2022)
This paper aims to explore the value chain of vegetables with the explicit objectives of observing actors' performance in the chain and examining vegetable supply factors in the market. The primary data were gathered from 150 value chain actors in the North-Eastern part of Bangladesh, using simple random and purposive sampling techniques. The major actors were input suppliers, producers, local traders (Paiker-1/Bepari, Arathdar, and Paiker cum retailers), and retailers. Input supply, production, marketing, and consumption were the typical value chain activities. Before reaching the end-users, a minimum value has been added to the products. A local trader named Paiker-1/Bepari governed the chain. They had a capital advantage over the other traders. The regression models' outcomes showed that marketable supply was significantly affected by the quantity of production and distance to market in tomato, cabbage, and cauliflower. However, in the case of beans, it was considerably affected by output, remoteness from the marketplace, and access to training.
Keywords: 650; Bangladesh; market supply; value chain; vegetables